2019
DOI: 10.1044/2018_jslhr-s-18-0299
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Native Language and the Fundamental Design of the Auditory System in Detecting Rhythm Changes

Abstract: Purpose We investigated whether rhythm discrimination is mainly driven by the native language of the listener or by the fundamental design of the human auditory system and universal cognitive mechanisms shared by all people irrespective of rhythmic patterns in their native language. Method In multiple experiments, we asked participants to listen to 2 continuous acoustic sequences and to determine whether their rhythms were the same or different (AX disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In line with this, Ordin et al. (2019) showed that in AX discrimination experiments, regular rhythm in the A stimulus (first stimulus in a stimulus pair) led to faster and more accurate responses, regardless of whether the X stimulus (second stimulus in a stimulus pair) was rhythmically similar to or different from the A stimulus. They suggested that rhythmic regularity in the first stimulus enhances attention and thus results in better performance.…”
Section: Introductionmentioning
confidence: 82%
“…In line with this, Ordin et al. (2019) showed that in AX discrimination experiments, regular rhythm in the A stimulus (first stimulus in a stimulus pair) led to faster and more accurate responses, regardless of whether the X stimulus (second stimulus in a stimulus pair) was rhythmically similar to or different from the A stimulus. They suggested that rhythmic regularity in the first stimulus enhances attention and thus results in better performance.…”
Section: Introductionmentioning
confidence: 82%
“…The sequences were paired into test stimuli, with a 1-s pause between the paired sequences. The pause duration was chosen based on Ordin, Polyanskaya, Gomez, and Samuel (2019) , who used a 1-s pause between stimuli with either similar or different rhythms in an AX rhythm discrimination experiment. We created 30 stimuli with paired sequences exhibiting Type A meter and 30 stimuli with paired sequences with Type B meter, that is, 60 stimuli with similar meter in both sequences.…”
Section: Methodsmentioning
confidence: 99%